2020
DOI: 10.1155/2020/8914372
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Assessments Used in Occupational Therapy Practice: A Global Perspective

Abstract: This exploratory study was aimed at evaluating the current status of global occupational therapy practice on the use of assessments for clients with cognitive impairments and providing recommendations for ongoing evidence. We targeted international occupational therapy clinicians working with clients experiencing neurocognitive impairments. 323 occupational therapists from a wide range of clinical practice areas participated in the study. A large number of therapists used noncognitive specific assessments with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
3
12
0
1
Order By: Relevance
“…The MoCA impaired and unimpaired groups approached but did not reach a significant difference based on sex. Due (Nasreddine et al, 2005) is a multi-component cognitive screening test that takes approximately 10 min to administer and is reported to be one of the most widely used cognitive screening tests by occupational therapists (Manee et al, 2020). The test evaluates eight domains of cognition including visuospatial and executive function, naming, memory, attention, language, abstraction, delayed recall and orientation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MoCA impaired and unimpaired groups approached but did not reach a significant difference based on sex. Due (Nasreddine et al, 2005) is a multi-component cognitive screening test that takes approximately 10 min to administer and is reported to be one of the most widely used cognitive screening tests by occupational therapists (Manee et al, 2020). The test evaluates eight domains of cognition including visuospatial and executive function, naming, memory, attention, language, abstraction, delayed recall and orientation.…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of this paper is to examine the degree to which performance on screening tests is associated with performance on a functional cognitive assessment, the WCPA. We selected three screening tests used by occupational therapists (Manee et al, 2020) based on their distinct screening methods: the MoCA (Nasreddine et al, 2005) uses a multi-domain brief battery approach, the Mini-Cog (Borson et al, 2000) limits assessment to two areas of cognitive functioning-short term word recall and executive functioning using a clock-drawing test, and the functional cognitive Menu Task (Edwards et al, 2019) uses a single multi-component selection activity conducted under rule constraints and that involves executive functioning (Al-Heizen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of brief global screening measures (e.g., Mini Mental State Exam, the Montreal Cognitive Assessment [MOCA], and the Neurobehavioral Cognitive Status Examination; Folstein et al, 1975;Kiernan et al, 1987;Nasreddine et al, 2005) to infer real-world IADL performance capacity is beyond the scope of the original purpose of the measures (Burgess et al, 2006). For example, the MOCA, one of the most widely used screening tests by occupational therapists (Manee et al, 2020), has been found to be of limited value in identifying the individuals with occupational performance problems and can result in both over and under identification of the potential for IADL impairment (Toglia et al, 2017;van der Wijst et al, 2014;Waldron-Perrine & Axelrod, 2012). Many neurocognitive tests were developed to assess intellectual ability or to identify brain lesions and were never intended to be used to evaluate the key elements of functional cognition needed to identify occupational performance deficits (Evans, 2010;Lezak et al, 2012).…”
Section: Relationship Of Neurocognitive Assessment To Performance-bas...mentioning
confidence: 99%
“…To date, several studies have been conducted to identify standardised assessment tools used by occupational therapists in different clinical areas, such as cognitive disability [ 16 , 17 , 18 ], mental health [ 19 ], geriatrics [ 20 ] and acute physical injury [ 21 ]. In addition, the use of assessment tools in occupational therapy practice has been explored in Anglo-Saxon countries, such as the United States, Australia, Canada, and New Zealand [ 16 , 21 , 22 , 23 , 24 , 25 ]. However, these studies have shown that around 10–30% of occupational therapists surveyed did not use standardised assessment tools in their daily clinical practice [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of assessment tools in occupational therapy practice has been explored in Anglo-Saxon countries, such as the United States, Australia, Canada, and New Zealand [ 16 , 21 , 22 , 23 , 24 , 25 ]. However, these studies have shown that around 10–30% of occupational therapists surveyed did not use standardised assessment tools in their daily clinical practice [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Moreover, some studies have raised a particular concern that the most widely used assessment tools in occupational therapy often have not undergone a formal process of validation in the context and/or population in which they are being used [ 17 , 21 ].…”
Section: Introductionmentioning
confidence: 99%